The Use of Artificial Intelligence (AI) In Marketing: An Empirical Study with The Construction of a Conversational Chatbot for Communication with The Client - Tomasz DRYL (Communications of International Proceedings, 2022)
Changes in the available communication technology take advantage of the possibilities of using artificial intelligence in the marketing process. One of the areas where artificial intelligence is used for customer service. The literature on the use of artificial intelligence in marketing applies in a similar way to the construction of conversational chatbots and their evaluation by customers. The research presented in the article prepare for the construction of conversational chatbots, as well as customer opinions on communication with chatbots. The main dimensions of customer communication with chatbots were examined and the results of the research were presented. The study involved 520 customers using communication with sales chatbots in the areas of insurance, telecommunications, IT and TV. The aim of the article is to present the process of constructing the marketing aspects of a conversational chatbot, to present the results of an opinion survey on the features of communication with a chatbot that enable automatic and machine sales. The results of the survey were presented, which made it possible to determine what directions of action should be taken by an organization using chatbots in the sales process.
Keywords: Artificial Intelligence; conversational chatbot in marketing; Artificial Intelligence in marketing